Karakterisasi mutu minuman jeli okra nanas dengan kombinasi karagenan-konjak[Characterization of pineapple okra jelly drink quality with different concentrations of carrageenan-konjac combination] - Amelia, Julfi Restu; Pujilestari, Shanti; Hamidatun, Hamidatun; Monica, Putri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
ABSTRACTOkra-pineapple jelly drink requires hydrocolloid as a gelling agent. The combination of carrageenan-konjac hydrocolloid used was 75:25 in order to produce acceptable and good quality jelly drink characteristics. This study aimed to characterize the quality of pineapple okra jelly drink with the addition of hydrocolloid (carrageenan-konjac combination). The concentration treatments of the carrageenan-konjac combination 75: 25 in this study were 0.6%, 0.7%, 0.8%, 0.9% and 1%. The research was carried out using a completely randomized design (CRD) experimental method with one factor and 3 replications. Data were analyzed statistically with ANOVA and Duncan multiple range test. The results showed that the concentration of the carrageenan-konjac combination had a significant effect on viscosity, water content, total dissolved solids, hedonic and scoring texture quality tests, but had no significant effect on pH, hedonic and scoring tests for color, taste and aroma. The best concentration of carrageenan-konjac combination in pineapple okra jelly drink was a concentration of 0.9% which had characteristics: viscosity 2488.33 cP, pH 4.05, water content 94.22%, total dissolved solids 5.10º Brix and sensory score from 3.9-4.2 (like) for color, aroma , taste and texture. This best treatment had greenish yellow color, fragrant aroma, sweet taste and slightly chewy texture. The supporting test in the form of antioxidant activity test (IC50) was 16.47 ppm indicated in the very strong category.